2013
DOI: 10.1093/bja/aet199
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of smart pumps for automated changeovers of vasoactive drug infusion pumps: a quasi-experimental study

Abstract: These results demonstrate the benefits of automated CVIP using smart pumps in limiting the frequency of haemodynamic incidents related to relays and in reducing the nursing workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 29 publications
2
55
0
6
Order By: Relevance
“…These strategies include good clinical practices, adequate training, and the optimal use of technologies. While two literature reviews suggest that smart pumps can contribute to a medication error risk reduction in healthcare settings [4,6], there are still limited data supporting such a risk reduction in the field [11][12][13][14][15][16][17][18][19][20]. Technologies are not free of risk and do create new failure modes [18].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include good clinical practices, adequate training, and the optimal use of technologies. While two literature reviews suggest that smart pumps can contribute to a medication error risk reduction in healthcare settings [4,6], there are still limited data supporting such a risk reduction in the field [11][12][13][14][15][16][17][18][19][20]. Technologies are not free of risk and do create new failure modes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Le retour aux valeurs de base est plus rapide aprè s un relais automatique qu'un relais manuel quelque soit le volume de la seringue (test Mann-Whitney, p < 0,05). embouts compressibles en caoutchouc ou les pistons de seringue contribue aussi à la pré cision des dé bits de mé dicament dé livré [12,13]. Enfin, la position en termes de hauteur du pousse-seringue par rapport au patient est susceptible de modifier les dé bits perfusé s. Krauskopf et al [14] ont montré expé rimentalement que le fait de suré lever une seringue autopulsé e de 100 cm é tait associé à l'é mission d'un bolus de 5 gouttes.…”
Section: Discussionunclassified
“…Il existe alors un risque d'une variation brutale de dé bit de mé dicaments avec potentiellement des consé quences sur la pression arté rielle. Cette variation du dé bit, qui a bien é té é valué e chez l'adulte, n'a pas fait l'objet de beaucoup de travaux chez le nouveau-né à terme encore moins chez le pré maturé [9,10] n'est pas exclusivement lié e à la duré e du changement de seringue habituellement brè ve < 1 min. Nous avons montré lors d'une é tude anté rieure que le dé lai de dé livrance effectif d'un mé dicament aprè s l'installation de la seringue dans le pousse seringue est trè s variable puisqu'il dé pend de l'ajustement du piston de la seringue dans le pousse seringue, du dé bit du mé dicament et du volume de la seringue [2].…”
Section: Introductionunclassified
“…Infusion is usually continuous through a central venous catheter (CVC), but there are no specific guidelines concerning infusion methods. Infusion onset, syringe changeover and flow rate changes are particularly critical due to the existence of mass flow rate disturbances [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This work showed differences in the time necessary to reach NE mass flow rate steady-state plateau after the onset of infusion or after a flow change and concluded that a combination of a low dead-space volume extension set and a double-pump method with a constant saline flow might be the solution to provide the most reliable NE infusion delivery. However, the limited capacity of syringes results in frequent changeovers, which induce high-risk periods of hemodynamic instability or arrhythmias due to interruption in drug delivery [1][2][3][4]9]. Hemodynamic instability after a changeover is a recurrent problem in intensive care units.…”
Section: Introductionmentioning
confidence: 99%